Международные неправительственные организации в системе современных международных отношений - Твердохлебов, Н.И. (Культура народов Причерноморья, 2003)
Over the past decade non-government organizations and their membership have grown hugely due to the social and economic shifts throughout the world. They have gone far beyond political activism delivering economic and technical services provided by the governments, intergovernmental organizations and multinational corporations. That’s why it’s important to analyse their different types, purposes, and forms of campaigning, relations with other international actors.